Asuhan Keperawatan Keluarga yang Mengalami Resiko Tinggi Perfusi Jaringan Serebral dengan Hipertensi di Wilayah Puskesmas Kecamatan Makasar - Aryanti Cristin; Herlina Herlina (STIKes Persada Husada Indonesia, 2021)
Hypertension is an increase in arterial blood pressure that is systematic or lasted continuously in the long term. Uncontrolled high blood pressure for a certain period will cause permanent high blood pressure called hypertension. Based on the visit of patients who came to Pinang Ranti Society Health Center in January – December 2017, the hypertension data as much as 2.060 (75.7%) of the people. The goal was did to a family nursing care that had a high risk of serebral system perfusion of hypertension in the area of society health center in Makasar subdistrict East Jakarta. The design of these research uses descriptive qualitative with intervention through case study approach. Data collection through; physical examination, interviews, documentation. The highest scoring result was found in family 2 that is 42/3 with high risk diagnosis of selebral system perfusion on Mr.I family’s b.d kmk treated family members with hypertension. Interventions conducted using provide health counseling, measurement of blood pressure, teach of stress management techniques and provide non-pharmacological therapy. Suggestions are expected the family’s can control their blood pressure regularly in the nearest society health center.